(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1993)
The simple Suzuki group Sz(2^2r+1) can be considered as a subgroup of the group of collineations of 3-dimensional projective space PG(3,2^2r+1) over GF(2^2r+1), fixing the special Tits ovoid t(ψ). This group determines a finite non-miquelian egglike Mobius plane J(o) of order q, consisting of points and plane sections f the above ovoid, when q=2^2r+1. In this paper a detailed picture of geometry of the subgroups of Sz(2^2r+1) is given with respect to the non-miquelian Mobius plane S(q)